A novel process route for the production of spherical SLS polymer powders - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of PPS-30 : the 30th International Conference of the Polymer Processing Society : conference papers : 6-12 June 2014, Cleveland, Ohio, USA, 2015)
Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) is promising. One drawback is the limited choice of polymer materials available as optimized powders. Powders produced by cryogenic grinding show poor powder flowability resulting in poor device quality. Within this account we present a novel proceb route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the proceb chain is demonstrated for polystyrene e. In a first step polymer microparticles are produced by a wet grinding method. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns. The applicability of this method will be discubed for different polymers and the dependencies of product particle size distribution on strebing conditions and proceb temperature will be outlined. The comminution products consist of microparticles of irregular shape and poor powder flowability. An improvement of flowability of the ground particles is achieved by changing their shape: they are rounded using a heated downer reactor. The influence of temperature profile and residence time on the product properties will be addrebed applying a viscous-flow sintering model. To further improve the flowability of the cohesive spherical polymer particles nanoparticles are adhered onto the microparticles' surface. The improvement of flowability is remarkable: rounded and dry-coated powders exhibit a strongly reduced tensile strength as compared to the comminution product. The improved polymer powders obtained by the proceb route proposed open new pobibilities in SLS procebing including the usage of much smaller polymer bead
Keywords: Downer reactor; Poly butylene terephthalate (PBT); Poly oxo methylene (POM); Polystyrene (PS); Rounding; Selective laser sintering (SLS); Wet grinding; rounding